Surveillance & Organisational Control: A Comparative Analysis of Uber and the Traditional Taxi Industry - Bugden, Jack (2017)
In the last decade, advancements in the mobility and implementation of technology have resulted in the expansion of the sharing-economy. The development of peer-to-peer platforms, such as the platform employed by Uber, have changed the nature of the business practise and provided sophisticated solutions to previous inefficiencies. However, the platforms also facilitate organisation’s ability to monitor and punitively control their employees - raising questions surrounding the true nature of the sharing-economy and its wider social impacts. The all-encompassing nature of the surveillance technology bears resemblance to Foucault’s disciplinary societies, panopticon theory and further conceptual extensions. This qualitative study compares the experiences of Uber drivers and traditional taxi drivers in Nottingham to investigate the impact of organisational control mechanisms, such as surveillance, on job satisfaction and autonomy. From analysing the findings, traditional taxi drivers felt greater freedom at work due to the less stringent form of surveillance practises. Uber drivers were attracted by the simplicity promoted by Uber in overcoming inefficiencies like corruption in the traditional taxi industry. There is evidence to suggest that the stringent nature of the control mechanisms and comprehensive surveillance techniques, utilised by Uber, compromise the driver’s autonomy and job satisfaction. The results provided insights into normalisation of surveillance in society, as well as participants sacrificing individual privacy for technological empowerment and mobility. As the sharing-economy and digital connectivity grows, the debate surrounding the conditions of our freedoms proliferates.